Comparisons between Asphalt Pavement Responses under Vehicular Loading and FWD Loading - Song Yang; Bing Qi; Zhensheng Cao; Shaoqiang Zhang; Huailei Cheng; Ruikang Yang (Advances in Materials Science and Engineering)
The strain responses of asphalt pavement layer under vehicular loading are different from those under falling weight deflectometer (FWD) loading, due to the discrepancies between the two types of loadings. This research aims to evaluate and compare the asphalt layer responses under vehicular loading and FWD loadings. Two full-scale asphalt pavement structures, namely, flexible pavement and semirigid pavement, were constructed and instrumented with strain gauges. The strain responses of asphalt layers under vehicular and FWD loadings were measured and analyzed. Except for field measurements, the finite element (FE) models of the experimental pavements were established to simulate the pavement responses under a wide range of loading conditions. Field strain measurements indicate that the asphalt layer strain under vehicular loading increases with the rising temperature roughly in an exponential mode, while it decreases with the rising vehicular speed approximately linearly. The strain pulses in the asphalt layer generated by FWD loading are different from those induced by vehicular loading. The asphalt layer strains generated by FWD loading are close to those induced by low vehicular speed (35 km/h). The results from the FE model imply that the asphalt layer strains under FWD loading and vehicular loading are distributed similarly in the depth profile. For flexible pavement, the position of critical strain shifts gradually from the bottom of the asphalt layer to the mid-depth of the layer, as the temperature increases. For semirigid pavement, the position of critical strain is always located at the intermediate depth of the asphalt layer, regardless of temperatures.